O učbenikih - Hladnik, Miran (Jezik in slovstvo, 2015)
The article summarises the author's experience in reviewing e-textbooks for Slovenian literature in elementary and secondary schools, as well as his experience in writing and editing academic textbooks. It criticises stereotype knowledge and expression, as well as the greed of publishing houses. Textbooks should be digital and open access.
Keywords: Slovene literature; slovenska književnost; univerzitetni učbeniki; prosti dostop; digitalni učbeniki